Genomewide Association Study of Severe Covid-19 with Respiratory Failure - Ellinghaus, David; Degenhardt, Frauke; Bujanda, Luis; Buti, Maria; Albillos, Agustín; Invernizzi, Pietro; Fernández, Javier; Prati, Daniele; Baselli, Guido; Asselta, Rosanna; Grimsrud, Marit M; Milani, Chiara; et al. (The New England journal of medicine, 2020)
During the peak of hospitalizations of patients with severe Covid-19 in Italy and Spain in March, a group of researchers in these and other countries obtained and analyzed samples, resulting in the identification of two chromosomal loci associated with the disorder.